Drowning risk assessment at a nature-based tourism destination in Malaysia: a case study of Chamang Forest-Eco Park - Zainal Abidin, Zulkhairi Azizi; Kelana, Siti Ratna; Ramlan, Mohd Aswad; Jumaat, Noor Jalilah; Aziz, Azlizam (Malaysian Forester, 2023)
Drowning poses a significant risk to tourism destinations and can harm the reputation and potential of ecotourism attractions. To manage this risk, a thorough drowning risk assessment is essential. This study assessed drowning risk factors at Chamang FEP using objective and subjective risk assessment methods. The objective assessment involved site observation, interviews, and a questionnaire based on Risk Assessment Management System (RAMS) conducted among the staff of Chamang FEP. The subjective assessment surveyed visitors' perceptions and acceptance of drowning risk management actions. Results showed that environmental and visitor hazards were important factors in fatal drownings at Chamang FEP, and high visitor numbers were perceived to play a key role in drowning safety management. The risk factors were consistent, demonstrating the appropriateness of the RAMS technique for assessing recreation risks at nature-based tourism destinations such as FEP.